FACTORS INFLUENCING THE REPORTING OF ABORTION CASES: PERSPECTIVESOF OBSTETRICIAN-GYNECOLOGISTS IN PERU - Cuba Varas, Lucero Carolina (2025)
Introduction. The criminalization of abortion in Peru poses ethical and legal dilemmas for healthcare professionals. Objectives. To evaluate the factors associated with the reporting of induced abortions and to explore the perceptions of obstetrician-gynecologists. Methods. A sequential mixed-methods study was conducted, with a quantitative phase followed by a qualitative one. One hundred obstetrician-gynecologists participated via a structured questionnaire, and ten were interviewed in depth. Variables included type of healthcare facility, perceptions of the General Health Law (GHL), prior experience, and attitudes toward reporting. Quantitative analysis used descriptive statistics, chi-square test, and Poisson regression with robust variance. Qualitative analysis followed an inductive thematic approach. Confidentiality, anonymity, and informed consent were ensured, in accordance with current ethical standards. Results. 28.0% of participants reported having notified an abortion case in the past ten years. Significant associations were found between reporting and having previously reported (PR=0.01; 95% CI: 0.00–0.05; p<0.001), not considering it necessary to inquire whether the abortion was induced (OR=0.84; 95% CI: 0.51–0.96; p=0.046), and knowing a colleague who had reported a case (OR=0.89; 95% CI: 0.62–0.98; p=0.012). The qualitative phase revealed discretion in clinical criteria, influence of stereotypes, patient fear of being reported, and institutional pressure, particularly in public facilities. Conclusion. The reporting of induced abortions is more strongly influenced by contextual and institutional factors than by clinical ones, underscoring the need for clear guidelines and the protection of professional confidentiality.